Computer-aided Planning and Execution in Facial Gender Surgery: Approaches, Concepts, and Implementation. Issue 5 (13th May 2022) - Louis, Matthew; Qiu, Cecil S.; Travieso, Rob; Marano, Drew; Coon, Devin
Abstract : Summary: Facial gender surgery (FGS) involves major surgical modification of the craniofacial soft tissues and skeleton. Computer-aided surgery (CAS) has improved precision and accuracy of osteotomies and decreased operative time in complex reconstructive craniofacial surgery. FGS is a natural application for CAS because the procedures are not only technically challenging but also demand a high standard of aesthetic results. Planning FGS cases virtually enables better and more reproducible results through simulated surgical planning and precise execution of osteotomies in surgical fields with limited exposure. We describe our experience with CAS in FGS for each of the facial thirds to introduce new concepts for conceptual planning of osteotomy design and patient-specific implants.